Critics and Experts, Activists and Academics: Intellectuals in the Fight for Social and Ecological Justice in the Narmada Valley, India - Pablo S . Bos e (IRSH 49 (2004), Supplement, pp. 133-157, 2004)
The following article examines the role of popular intellectuals in the rise of the Narmada Bachao Andolan, a mass-based movement opposed to the building of large dams in the Narmada Valley of central India. In particular, it focuses on two of this struggle's most prominent public figures and spokespersons, Medha Patkar and Arundhati Roy. The article examines the relationship between these individuals and the movement itself - how issues have been framed by Patkar and Roy for local, national, and international audiences, how support for the antidam struggle has been mobilized, and how each of these figures are themselves perceived and portrayed. The article will also examine some of the challenges faced by the movement and its leaders, not only from proponents of the dam projects, but also from other social activists and intellectuals. The latter have raised questions about representation, voice and strategy, as well as insider/outsider authenticity and legitimacy in the anti-dam movement, issues that this paper considers in some detail. Finally, the article draws on the Narmada case to ask some broader questions regarding popular intellectuals and social movement organizing and strategy.